Institutional Conscientious Objection is Not the Answer. - Wicclair, Mark (American Journal of Bioethics, 2026)
This article critically examines the justification for recognizing institutional conscience rights—claims based on deeply held moral values—specifically for secular healthcare institutions refusing treatment requests for neurologically devastated patients, defined as those permanently unconscious or declared dead by neurological criteria. The authors argue that secular institutions, like religious ones, can experience a form of moral harm analogous to individual clinicians’ conscience-based distress, warranting accommodation of their refusals. However, the article raises concerns about whether institutional conscience claims provide clear, consistent standards, potentially deny surrogates a fair hearing, and risk limiting patient access to legally accepted care. It also highlights the broader implications of legitimizing institutional conscientious objection, which could complicate healthcare delivery and patient access, emphasizing the need for carefully defined constraints to balance institutional conscience with patient rights.